ANALISIS KESULITAN MENULIS DALAM MATERI AKSARA JAWA KELAS IV SD NEGERI BLEKATUK - Muhamad Baqda Maulana Yahya; Nur Ngazizah; Titi Anjarini (STKIP Subang, 2026)
This study aims to analyze: (1) To analyze in a detailed and comprehensive manner the difficulties students face in writing Javanese script material in Grade IV elementary school. (2) To identify the factors that cause students’ difficulties in writing Javanese script material in Grade IV elementary school.The type of research used in this study is qualitative research with a descriptive method. The data collection techniques used include data analysis through observation, interviews, tests, and documentation. The total number of Grade IV students is 19, and 8 students were selected. The results of the study, which involved 8 students, show that: 1) the difficulties in writing Javanese script include, for subject 1, having difficulty using the vowel diacritic 'o', and for subjec 2) Subject 2 had difficulty using the vowels E, U, I; Subject 3 did not understand Javanese script; Subject 4 had difficulty using the vowels O, E, U; Subject 5 had difficulty using the vowels U and E; Subject 6 had difficulty using the vowels O, E, U; Subject 7 had difficulty using the sign that should use the 'suku' on the 'ra' character but instead used 'wulu', which sounds like 'i'; Subject 8 had difficulty writing Javanese script, with answers 1 to 5 being unreadable. 2) Factors influencing writing difficulties include not memorizing Javanese script, minimal practice, and complex shapes.